2018
DOI: 10.12659/msm.906666
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Quality of Sexual Life Questionnaire for Breast Cancer Survivors in Mainland China

Abstract: BackgroundThere is a great need for a quality of sexual life questionnaire (QVS) in breast cancer survivors (BCSs) based on the Chinese social culture since the imported tools lack localization verification.To develop a QVS in BCSs and determine its validity and reliability.Material/MethodsIn the qualitative study, a total of 21 BCSs were interviewed by purposive sampling and snowball sampling; and in the quantitative study, a total of 249 BCSs, who were admitted and received outpatient follow-up, were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…To compare the components of sexual responses between Malaysian women with type 2 diabetes mellitus and those without the disease Jing et al 46 Breast cancer survivors 246 To develop a Quality of Sexual Life Questionnaire in Breast Cancer Survivors and determine its validity and reliability Kalmbach et al 47 Female undergraduate students 409 To assess factor structures of the FSFI, MSFI (adapted for this investigation), and PFSF in young, healthy men and women Likes et al 48 43 93 PCA FSFI-19: Unrotated PCA identified five components. Although the sixth component had a considerably low eigenvalue, subsequent equamax rotation yielded the most consistent pattern of factor loadings using a 6-component structure.…”
mentioning
confidence: 99%
“…To compare the components of sexual responses between Malaysian women with type 2 diabetes mellitus and those without the disease Jing et al 46 Breast cancer survivors 246 To develop a Quality of Sexual Life Questionnaire in Breast Cancer Survivors and determine its validity and reliability Kalmbach et al 47 Female undergraduate students 409 To assess factor structures of the FSFI, MSFI (adapted for this investigation), and PFSF in young, healthy men and women Likes et al 48 43 93 PCA FSFI-19: Unrotated PCA identified five components. Although the sixth component had a considerably low eigenvalue, subsequent equamax rotation yielded the most consistent pattern of factor loadings using a 6-component structure.…”
mentioning
confidence: 99%
“…Sexual distress was psychological and emotional distress caused by sexual dysfunction (Sears et al, 2018). Sexual quality of life was defined as an individual’s subjective evaluation and perception on sex‐related physiology, psychology and social culture (Jing et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Sexual quality of life was defined as an individual's subjective evaluation and perception on sex-related physiology, psychology and social culture (Jing et al, 2018).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Sexual quality of life is the person’s assessment of positive and negative aspects of their sexual life and their response to this assessment [ 1 ]. Sexual quality of life is tightly interwoven with the extent of satisfaction with life and general level of quality of life [ 2 ].…”
Section: Introductionmentioning
confidence: 99%